Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1590/s1516-18462009000600011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da fluência verbal em crianças com transtorno da falta de atenção com hiperatividade: um estudo comparativo

Abstract: OBJETIVO: comparar o desempenho de indivíduos com TDAH e grupo controle, em provas de fluência verbal, na faixa etária de 7 aos 12 anos, sem déficit cognitivo. MÉTODOS: foram avaliadas 22 crianças com TDAH e 34 do grupo controle, estudantes de escolas públicas no Estado do Rio de Janeiro. Aplicou-se uma prova de fluência verbal, subdividida em avaliação da fluência fonológica e semântica, sendo utilizada a letra F na prova fonológica e a categoria Animais na prova semântica. Os testes de fluência verbal avalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…Thus, it has been used for cognitive screening and aid in diagnosis for various diseases, such as attention deficit hyperactivity disorder, Parkinson's disease, schizophrenia, cognitive impairment, and bipolar disorder (12)(13)(14)(15)(16) . No reports are available about the application of this test in the hearing-impaired individuals, or about the possible variables that affect the performance of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been used for cognitive screening and aid in diagnosis for various diseases, such as attention deficit hyperactivity disorder, Parkinson's disease, schizophrenia, cognitive impairment, and bipolar disorder (12)(13)(14)(15)(16) . No reports are available about the application of this test in the hearing-impaired individuals, or about the possible variables that affect the performance of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…C C PC PC C Kibby MY, Kroese JM, Krebbs H, Hil CE, Hynd GW (16) . C PC C C C Silveira DC, Passos LMA, Santos PC, Chiappetta ALML (17) .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they stress the crucial importance of instituting programs to provide support to these professionals so the best assistance can be offered to individuals with ADHD, thus minimizing the deficits associated with this condition as a result of the behavioral difficulties that involve neurobiological alterations 5 . Previous studies correlating ADHD with the development of written language concluded that the most prevalent learning disabilities compromise the areas of reading (8%-39%) and writing (60%) 3,5,6 . Moreover, those studies enabled hypotheses proposing that the language deficits in children with ADHD may be directly linked to cognitive activities coordinated by organized behaviors including aspects of speech 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Reflecting the behavioral features manifested by children with ADHD, it is in the school environment that the restlessness and impulsivity are seen as indiscipline and disrespect for the community norms, and the inattention as carelessness, since these symptoms can be observed previously to pre-school 6 . However, the parents and professionals who assist these children may have difficulty establishing the diagnosis of ADHD before the child experiences environments other than the family household.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation